Competitiveness and Knowledge in Theory and Practice - Westeren, Knut Ingar (Informe GEPEC, 2000)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This chapter is about competitiveness in theory and in reality at the firm level. The competitive situation of the firm has always been vital to the firm’s development while the more theoretical discussions have changed in intensity. One upswing of the theoretical debate came in the 1980’s with the introduction of the work by Porter and this debate is still continuing. One result so far seems to that most scientists are critical to transfer the concept of competitiveness from the micro/firm level to the macro level. There still seems to be two points of departure (or “schools”) for how to conceptualize competitiveness. One has been called the industrial economy school linked to Porter and the other using a resource/competence view of the firm, several scientists can be named here, e. g. Penrose and Hunt. In this chapter we discuss similarities and differences between these schools. After 2000 we have seen several statements from the European Union and others about how developed economies actively must utilize the knowledge base of the communities they are a part of to develop competitiveness. In the empirical part of this chapter we show how that can be done. This analysis is done within the framework of a resource/competence based view of the firm where it is important to develop competence depending on changing needs from the market.